Pendidikan dan Penyuluhan tentang Menepis Rumor Vaksinasi Covid-19 di Kotagede Yogyakarta - Ubaidillah Ubaidillah (Humanism: Journal of Community Empowerment (HJCE), 2022)
The pros and cons of vaccines are becoming increasingly popular and are being discussed. There is a lot of debate, especially on social media. Even some health workers still have different opinions about this vaccine, especially ordinary people. Many people say that vaccine is haram, because it is made from haram ingredients or elements such as enzymes or pork trypsin, or other haram ingredients. Then there are many opinions that vaccine is a conspiracy of a certain country or ethnic group that will bring down a certain religion or ethnicity as well. Beside that many people say vaccines are dangerous because they contain certain substances that can cause a person or a child to become disabled or hyperactive, and there is business behind of this vaccine. The purpose of this community service is to provide the education properly to the people in Kotagede, so that they know and understand about this vaccine and do not get hoax news. The method used presentation, question and answer method. The results of this counseling showed that there was an increase in knowledge about vaccinations, vaccine rumors, where after distributing the questionnaires there was an increase in knowledge of 80% from the beginning before the presentation which was only 50%. The conclusion of this community service program with counseling will increase public knowledge about vaccines, because vaccines are to improve our immune system. Keywords: Vaccine, antigen, pork trypsin, Covid-19